Chronic kidney disease mortality trends in selected Central America countries, 1997–2013: clues to an epidemic of chronic interstitial nephritis of agricultural communities. Issue 4 (2nd February 2018) - Ordunez, Pedro; Nieto, F Javier; Martinez, Ramon; Soliz, Patricia; Giraldo, Gloria P; Mott, Susan Anne; Hoy, Wendy E
Abstract : Background: In Central America, chronic interstitial nephritis of agricultural communities (CINAC) has reached epidemic proportions. Clusters of cases have been described in several farming communities. Its aetiology remains uncertain and a controversy exists on its key triggers, among them the heat stress–dehydration mechanism and the toxic exposure to agrochemicals. Methods: This study analysed the mortality pattern and trend of chronic kidney disease code N18 (CKD-N18) according to the International Statistical Classification of Diseases and Related Health Problems-10th Revision, the proxy and the underlying cause of death, in four selected Central American countries from 1997 to 2013. In addition, we used exponential regression to retrospectively model the likely onset and prior trajectory of the epidemic. Results: Between 1997 and 2013, CKD-N18 mortality accounting 47 885 deaths (31% were female), 19 533 of which occurred below 60 years of age (26% female). The excess of mortality starts as early as 10–14 years of age for both boys and girls. El Salvador and Nicaragua, with mortality rates between 9-fold and 12-fold higher than reference countries, were the most affected. Statistical modelling suggests that the epidemic commenced around the mid-1970s, coinciding with important changes in modes of agricultural production. Conclusions: This study provides the most comprehensive mortality analysis of this epidemic published to date and confirms an excess of CKD-N18 mortality and its relation with the epidemic of CINAC. The overall trends and the mortality pattern among women, children and adolescents suggest that the heat stress–dehydration hypothesis cannot fully explain this epidemic and that other environmental factors, more likely agricultural practices and agrochemicals, may be causally involved.